2016
DOI: 10.21037/tlcr.2016.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenetic therapies for central nervous system metastases from non-small cell lung cancer

Abstract: Central nervous system (CNS) metastases are common in patients with advanced non-small cell lung cancer (NSCLC), occurring in 24% to 44% of patients in the course of their disease and confer significant morbidity and mortality. Systemic therapies have been deemed ineffective in brain metastases (BM) under the hypothesis that the blood-brain barrier (BBB) limits their delivery to the brain. Angiogenesis, which is mainly mediated by vascular endothelial growth factor (VEGF) pathway, is crucial for tumor survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 83 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…Tumor vascularization is critical to the pathogenesis of solid tumors, and TMD is related to tumor invasiveness and metastasis formation which could be used as a potential predictive marker for bevacizumab benefit [ 38 ]. This antagonistic effect of VEGF inhibit immature angiogenesis and induce vascular normalization, thus increasing the internal perfusion of the tumor and increasing the rate of drug delivery [ 39 ]. In theory, bevacizumab increases the rate of drug entry into the brain, combined with osimertinib possibly have more advantageous in the control of intracranial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor vascularization is critical to the pathogenesis of solid tumors, and TMD is related to tumor invasiveness and metastasis formation which could be used as a potential predictive marker for bevacizumab benefit [ 38 ]. This antagonistic effect of VEGF inhibit immature angiogenesis and induce vascular normalization, thus increasing the internal perfusion of the tumor and increasing the rate of drug delivery [ 39 ]. In theory, bevacizumab increases the rate of drug entry into the brain, combined with osimertinib possibly have more advantageous in the control of intracranial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Both univariate and multivariate analyses showed that the use of bevacizumab was a good prognostic factor for NSCLC LM patients with combination therapy. Bevacizumab is a recombinant humanized IgG1 monoclonal antibody against vascular endothelial growth factor (VEGF), which specifically binds to VEGF to block its binding to its receptor, thus reducing angiogenesis, inducing the degeneration of existing blood vessels, inhibiting tumour formation, inhibiting immature angiogenesis, and inducing vascular normalization [ 24 ]. Animal studies have shown that antiangiogenic treatment can prolong the survival time of LM mice [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, apatinib was well tolerated in all patients, and no grade 3/4 AEs were observed. Cerebral hemorrhage is one of the most common side effects in patients who receive antivascular therapies 36,37 . However, no cerebral hemorrhage and no other severe AEs were documented in all enrolled patients.…”
Section: Discussionmentioning
confidence: 99%